Do Mergers Matter? Financial Performance Insights from Financial and Non-Financial Sector Firms Listed in Indonesia Stock Exchange - Loebiantoro, Ika Yanuarti; Dewi, Helena; Kurniasari, Florentina; Jagge, January Reza; Lestari, Elissa Dwi (Indonesian Journal of Sustainability Accounting and Management, 2025)
The COVID-19 pandemic significantly impacted global business activities, including a sharp decline in successful mergers and acquisitions (M&A), with failure rates reaching 70–90% in 2020. Despite this, a notable number of M&A transactions still occurred in Indonesia, especially within the financial and non-financial services sectors. This study compares company performance before and after mergers, using market ratios: Price-to-Earnings Ratio (PER), Price-to-Sales Ratio (PSR), and Price- to-Book Ratio (PBV), as indicators of potential returns and risks for investors. The sample consists of Indonesian companies that merged in 2020 and are listed on the Indonesia Stock Exchange, with financial statements available for three years before and after the merger. Data were analyzed using the Kolmogorov-Smirnov test, followed by the Wilcoxon Signed-Rank Test. The results show no significant differences in PER, PSR, or PBV pre- and post-merger. This study contributes to the literature by highlighting the limited effectiveness of mergers, particularly during crisis periods, and provides practical insight into the use of market ratios for evaluating merger success from an investor’s perspective.